Physico-chemical litter amendments and their impact on broiler chicks’ performance - BABU, RUDRA NARAYAN; KAUR, DALJEET; UNIYAL, SANDEEP; KAUR, PAVITER; SINGH, YASHPAL; KAUR, PARAMJIT; MALIK, D S (The Indian Journal of Animal Sciences, 2023)
The objective of the study was to compare the effects of alternative litter treatments on litter quality, growth, carcass traits and welfare of broiler chicks. Day old, commercial broiler chicks (180) having similar body weight range were randomly allocated to two different types of litter treatments, viz. treated litter at the rate of 120°C (T1) and litter treated with sodium bisulfate 25 g/sq. ft. (T2) along with the control group without any litter treatment (T0). Birds of all the treated groups performed better in terms of growth, feed intake and FCR, etc. Cake formation was frequent, highest in T0 followed by T1 and T2 groups which in turn affected the frequency of undesirably poor sanitary outlook of the birds. Significantly lower EPG (E. coli count per gram) count while a numerically lower microbial load of the faecal samples was noted in the T2 than T1 and control. This implied the change in the pH and acidification of litter materials prevented the growth of coccidia and microbial load in the litter, thus making the litter more suitable for bird welfare. It was concluded that chemical litter amendments had a beneficial effect on overall growth performance, carcass characteristics, health and welfare of broiler chicks.